Development of Delay and Disruption Cause Monitoring Framework for Megaprojects: A Claim Management Approach from the Contractor's Perspective to Enhance Sustainability in the Built Environment - Okudan, Ozan; Cevikbas, Murat; Isik, Zeynep (MDPI, 2024)
Delays and disruptions (D&D) are considered chronic peculiarities of the construction phase of the built environment, especially in megaprojects. Systematic monitoring of claimable D&D causes becomes crucial for the contractors to compensate for their losses caused by delays and disruptions, enabling sustainable use of resources. Thus, this study proposed a delay and disruption (D&D) cause monitoring framework that enables contractors to timely and accurately detect claimable delays and disruption causes/events in megaprojects. At the outset, a systematic literature review was conducted to design an initial version of the framework and extract claimable D&D. Then, focus group discussion (FGD) sessions were conducted to revise and refine the initial version of the framework and a list of claimable D&D causes. Next, a fuzzy Analytical Hierarchy Process (AHP) analysis was conducted to determine the relative importance of each claimable D&D cause in terms of its impact on the megaprojects. Finally, a consistency analysis was conducted to demonstrate the reliability of the dataset. Findings revealed that claimable D&D causes are indispensable parts of the claim management process. In this manner, the proposed framework recommends monitoring the claimable D&D causes regularly during the whole construction phase of the megaprojects. The fuzzy AHP analysis also revealed that causes such as Suspension of project activities by the owner, Errors and clashes in the design, Shortage of construction materials in the market, Discovery of fossils and historical artifacts, Unavailability of the commissioning team on the due date, and Late delivery of testing materials and utilities by the owner were particularly rated as highly critical causes, needing urgent and sophisticated monitoring plan for timely detection and data collection. By introducing a proactive approach to avoid lengthy and costly dispute resolution processes, this study enables decision-makers to enhance sustainability in the built environment.
Keywords: built environment; sustainable development; sustainable project management; sustainable infrastructure; megaprojects; delay management; disruption management; claim management; fuzzy AHP; MCDM; CONSTRUCTION PROJECTS; SCHEDULE DELAY; FUZZY; SYSTEMS; DESIGN; MODEL; Science & Technology - Other Topics; Environmental Sciences & Ecology